Aflatoxin M1 in milk and dairy products: global occurrence and potential decontamination strategies. (3rd April 2022) - Muaz, Khurram; Riaz, Muhammad; Oliveira, Carlos Augusto Fernandes de; Akhtar, Saeed; Ali, Shinawar Waseem; Nadeem, Habibullah; Park, Sungkwon; Balasubramanian, Balamuralikrishnan
Abstract: Aflatoxin M1 (AFM1 ) is a hepatocarcinogenic compound found in milk from lactating individuals receiving diets contaminated with aflatoxin B1 . Considering the AFM1 resistance to conventional processing methods applied to milk products, novel approaches have been proposed to efficiently decontaminate AFM1 . This review focuses on recent occurrence data of AFM1 and the physical, chemical and biological methods for decontamination of AFM1, in milk and dairy products. Occasionally, high AFM1 occurrence levels have been reported, mainly in African countries. Adsorption through nonviable microorganisms and clay materials are the most effective, promising approaches for decontamination of AFM1 from milk and dairy products.